Ruptured ectopic pregnancy with leiomyoma history Gynecological Emergency: A Case Report - Seprializa, Seprializa; Dinna, Karlina; J, Nabila Farah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
An Ectopic pregnancy (EP) is a life-threatening gynecological emergency and a major cause of maternal mortality and morbidity all over the world. A high index of suspicion is curcial during the first trimester of pregnancy. A 29 year old woman came to emergency department with complaints severe abdominal pain and vaginal bleeding, along with a positive pregnancy test at 8 weeks gestational age. The patient had misscariage history in prior pregnancy. Physical examination revealed abdominal tenderness and blood on OUE. Two weeks prior, an Transvaginal ultrasound (TVS) showed no gestational sac but thickening of the uterine wall, and a recent TVS indicated a collapsed gestational sac, hematocel, and hemoperitoneum. TVS also showed intramural uterine myoma in size 5x3cm. Disturbed EP with uterine leiomyoma or fibroid was confirmed with physical examination and TVS. We performed a successful laparotomy, salpingectomy, and myomectomy, with no complications. Surgical treatment was perfomed in this patients based on data suggestive of hemoperitoneum. Leiomyoma don’t directly cause ectopic pregnancy but potentially increase the risk. The clinical features along with identification of risk factors like leiomyoma and TVS imaging can confirm the diagnosis of EP. TVS can be helpful for early detection and guide treatment to improve the patient's hemodynamics.